Continuous flow nitration in miniaturized devices - Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2014)
This review highlights the state of the art in the field of continuous flow nitration with miniaturized devices. Although nitration has been one of the oldest and most important unit reactions, the advent of miniaturized devices has paved the way for new opportunities to reconsider the conventional approach for exothermic and selectivity sensitive nitration reactions. Four different approaches to flow nitration with microreactors are presented herein and discussed in view of their advantages, limitations and applicability of the information towards scale-up. Selected recent patents that disclose scale-up methodologies for continuous flow nitration are also briefly reviewed.
Keywords: continuous flow; flow chemistry; microreactors; nitration; nitric acid; Tubular reactor

Evaluation of multipoint dosing strategy in a miniaturized tubular reactor: nitration of salicylic acid - Debnath, Soujoy; Kienle, Achim; Kulkarni, Amol A. (Chemical Engineering & Technology, 2014)
A 2D non-isothermal reaction engineering model for a tubular reactor was developed for a complex reaction network of salicylic acid nitration. The influence of different operating and design parameters was studied to minimize the amount of secondary nitration products and limit the maximum temperature inside the reactor. Critical temperature effects were observed for larger reaction tubes, whereas close to isothermal conditions were perceived in smaller tubes. With single-point dosing of both reactants, complete conversion can be achieved but formation of secondary nitration products cannot be avoided. For a given number of dosing points, a suitable combination of the operating parameters allowed to achieve complete conversion and better yield of the desired product.
Keywords: Multipoint injection; nitration; Plug-flow reactor; Salicylic acid; Tubular reactor

Continuous flow synthesis of micron size silica nanoparticles: parametric study and effect of dosing strategy - Jundale, Rajashri; Bari, Atul; Thara, Chinnu; Kulkarni, Amol (Journal of Flow Chemistry, 2018)
This work for the first time reports continuous flow synthesis of silica nano-particles of size over 1 mu m using a simple tubular reactor. The systematic approach involves the study of effect of various parameters like: ammonia concentration, water concentration, electrolyte concentraton, temperature, solvent, residence time and mode of TEOS injection over a wide range. A combination of ethanol and butanol was used as the medium with relatively lower polarity. Various process parameters were optimized to obtain highly monodispersed particles of size up to 600 nm and high yield (up to 90%). Attempts of reducing the reaction time by increasing temperature or concentrations of any of the reagents resulted in significant polydispersity and even in the formation of random shape agglomerates. At the optimized conditions almost complete conversion of TEOS happenned within 40 min and further growth of particles was achieved by adding TEOS using multipoint injection approach. While multipoint dosing resulted in the formation of very small number of secondary particles, the larger particles continued to grow beyond 800 nm. Further reduction in the polarity of reaction medium was achieved by adding 20% v/v of toluene, which without changing homogeneity of the solution resulted in particles as large as 0.9-1.1 mu m.
Keywords: Flow synthesis; Multipoint injection; silica; TEOS; Tubular reactor

Continuous flow synthesis of hierarchical low silica X zeolite - Adarsh, V. K.; Shrotri, Aadesh R.; Birje, Amit R.; Nandanwar, Sachin U. (Materials Today Communications, 2024)
Zeolites, renowned for their versatile applications in catalysis, adsorption, and ion exchange, have long been synthesized using conventional batch processes. However, the inherent limitations of these methods, such as resource-intensive conditions and inconsistent product quality, underscore the need for a sustainable and efficient approach. In this study, a continuous flow synthesis process was established for the synthesis of industrially important low silica X (LSX) zeolite using a tubular reactor. The synthesis gel was subjected to aging for 5 days at room temperature to facilitate nucleation and crystal growth combined with the fast-heating rate in a tubular reactor at 363 K & 1.1 atm., which in turn produces LSX after 40 min. The synthesized product was confirmed by the XRD, FE-SEM, EDS, XRF, TEM, and N2 adsorption-desorption; the data was compared with the LSX sample synthesized by batch process. The result implies that LSX prepared by continuous flow has a pure phase of LSX with the hierarchical structure, which provides better adsorption capacity of CO2 at 298 K up to 20 bar. Due to continuous flow synthesis, the crystallization time was reduced and faster kinetics which may be helpful for scale-up the process for LSX synthesis.
Keywords: Adsorption; Carbon dioxide; continuous flow; Low silica X; Tubular reactor; zeolites